Osteo-taxonomic distinction of fishes of the family Leiognathidae - James, P.S.B.R. (Indian Journal of Fisheries, 2011)
The subtle external taxonomic differences between closely resembling species of Leiognathidae have been osteologicallysubstantiated by highlighting the differences in the skull bones. Amongst them, the vomer, epiotic, basisphenoid and palatinewere found to be characteristic of most of the species.